Ascorbic acid and ascorbate-2-phosphate decrease HIF activity and malignant properties of human melanoma cells. Issue 1 (December 2015) - Miles, Sarah; Fischer, Adam; Joshi, Sandeep; Niles, Richard
Abstract Background Hypoxia inducible factor-1 alpha (HIF-1α) is thought to play a role in melanoma carcinogenesis. Posttranslational regulation of HIF-1α is dependent on Prolyl hydroxylase (PHD 1–3) and Factor Inhibiting HIF (FIH) hydroxylase enzymes, which require ascorbic acid as a co-factor for optimal function. Depleted intra-tumoral ascorbic acid may thus play a role in the loss of HIF-1α regulation in melanoma. These studies assess the ability of ascorbic acid to reduce HIF-1α protein and transcriptional activity in metastatic melanoma and reduce its invasive potential. Methods HIF-1α protein was evaluated by western blot, while transcriptional activity was measured by HIF-1 HRE-luciferase reporter gene activity. Melanoma cells were treated with ascorbic acid (AA) and ascorbate 2-phosphate (A2P) to assess their ability to reduce HIF-1α accumulation and activity. siRNA was used to deplete cellular PHD2 in order to evaluate this effect on AA's ability to lower HIF-1α levels. A2P's effect on invasive activity was measured by the Matrigel invasion assay. Data was analyzed by One-way ANOVA with Tukey's multiple comparisons test, or Student-T test as appropriate, with p < .05 considered significant. Results Supplementation with both AA and A2P antagonized normoxic as well as cobalt chloride- and PHD inhibitor ethyl 3, 4-dihydroxybenzoate induced HIF-1α protein stabilization and transcriptional activity. Knockdown of the PHD2 isoform with siRNA did not impede the ability of AA to reduce normoxic HIF-1α protein. Additionally, reducing HIF-1α levels with A2P resulted in a significant reduction in the ability of the melanoma cells to invade through Matrigel. Conclusion These studies suggest a positive role for AA in regulating HIF-1α in melanoma by demonstrating that supplementation with either AA, or its oxidation-resistant analog A2P, effectively reduces HIF-1α protein and transcriptional activity in metastatic melanoma cells. Our data, while supporting the function of AA as a necessary cofactor for PHD and likely FIH activity, also suggests a potential non-PHD/FIH role for AA in HIF-1α regulation by its continued ability to reduce HIF-1α in the presence of PHD inhibition. The use of the oxidation-resistant AA analog, A2P, to reduce the ability of HIF-1α to promote malignant progression in melanoma cells and enhance their response to therapy warrants further investigation.